Integrasi Dimensi Etis dan Praktik Konseling Pastoral Kontemporer Konteks Lingkungan Gereja - Santoso, Christopher; Herman, Samuel (Jurnal Teologi Kontekstual Indonesia, 2024)
The issue of integrity and ethics in pastoral counseling services is a major concern in the contemporary church context. Various cases of ethical violations within the church environment highlight a gap in the application of moral and ethical values, which should serve as the foundation of pastoral ministry. Therefore, this study aims to explore how ethical values can be effectively integrated into pastoral counseling practices to create a more dignified and responsible church environment. This research employs a qualitative method with a literature review approach, analyzing various theological and academic sources related to pastoral ethics, church leadership, and counseling dynamics within the Christian community. The study also examines moral principles rooted in the Bible as the primary guideline for pastoral ministers in guiding congregants. The findings indicate that the integration of ethics in pastoral counseling heavily relies on a deep understanding of Christian moral principles and the strict application of ethical standards in interactions between church leaders and congregants. By emphasizing the character of Christ as the primary model in pastoral ministry, the church can develop counseling practices that are more effective, ethical, and aligned with Christian values.